Only earth and sky last forever. - Benchley, Nathaniel, 1915- (Harper & Row, 1972)
Although recognizing the end of the Indians' freedom is near, a young Cheyenne still chooses to fight with Crazy Horse at the Little Big Horn to prove himself to the girl he loves.